Analisis E-Service dan Kepercayaan Konsumen terhadap Kepuasan Konsumen Pengguna Website - Tegar Maulidi Putra; Asep M. Ramdan; Faizal Mulia (BUDGETING : Journal of Business, Management and Accounting, 2019)
The purpose of this study is to determine the effect of e-service quality and consumer confidence on customer satisfaction. The use of the method in this study is to use a type of sampling included in the sample random sampling and by distributing questionnaires as many as 96 to consumers. The analysis technique used is multiple linear analysis techniques, and for hypothesis testing is a statistical test partial (t test) and simultaneous testing (f test). T test results show that e-service quality (X1) has a significant effect on customer satisfaction, consumer confidence (X2) has a significant effect on customer satisfaction. Based on the F test the probability value sig 0,000 <0.10 which means that together e-service quality (X1) and consumer confidence (X2) significantly influence consumer satisfaction (Y). Conclusion, together e-service quality and consumer trust significantly influence consumer satisfaction Keywords: E-Service Quality, Consumer Trust, Consumer Satisfaction.